Juglans mandshurica Maxim.: A Review of Its Traditional Usages, Phytochemical Constituents, and Pharmacological Properties - Fei Luan; Fei Luan; Ziyan Wang; Yan Yang; Yafei Ji; Haizhen Lv; Keqing Han; Daoheng Liu; Xiaofei Shang; Xirui He; Nan Zeng (Frontiers Media S.A., 2021)
Juglans mandshurica Maxim., also known as "Manchurian walnut" (Chinese) and "Onigurumi" (Japanese), is a medicinal plant widely distributed in Western and Central Asia, especially in China. It has been traditionally used to treat cancer, gastric ulcers, diarrhea, dysentery, dermatosis, uterine prolapse, and leukopenia. To date, more than 400 constituents including quinones (e.g. naphthoquinones, anthraquinones, naphthalenones, tetralones), phenolics, flavonoids, triterpenoids, coumarins, lignans, phenylpropanoids, diarylheptanoids, and steroids, were isolated and structurally identified from different plant parts of J. mandshurica. Among them, quinones, phenolics, triterpenoids, and diarylheptanoids, as the major bioactive substances, have been extensively studied and displayed significant bioactivity. Previous studies have demonstrated that J. mandshurica and a few of its active components exhibit a wide range of pharmacologically important properties, such as antitumor, immunomodulatory, anti-inflammatory, neuroprotective, anti-diabetic, antiviral, antimicrobial, and anti-melanogenesis activities. However, many investigations on biological activities were mainly based on crude extracts of this plant, and the major bioactive ingredients responsible for these bioactivities have not been well identified. Further in vitro and in vivo studies on the mechanisms of action of the pure bioactive compounds, and more elaborate toxicity studies as well as clinical studies are needed to ensure safety and effectiveness of the plant for human use. Taken together, the present review will provide some specific useful suggestions guide to further investigations and applications of this plant in the preparation of medicines and functional foods.